Recent advances in epigenetic anticancer therapeutics and future perspectives - Ren, Liwen; Yang, Yihui; Li, Wan; Yang, Hong; Zhang, Yizhi; Ge, Binbin; Zhang, Sen; Du, Guanhua; Wang, Jinhua (Frontiers in Genetics, 2023)
Tumor development is frequently accompanied by abnormal expression of multiple genomic genes, which can be broadly viewed as decreased expression of tumor suppressor genes and upregulated expression of oncogenes. In this process, epigenetic regulation plays an essential role in the regulation of gene expression without alteration of DNA sequence, including DNA methylation, RNA methylation, histone modifications and noncoding RNAs. Therefore, drugs developed for the above epigenetic modulation have entered clinical use or preclinical and clinical research stages, contributing to the development of antitumor drugs greatly. Despite the efficacy of epigenetic drugs in hematologic caners, their therapeutic effects in solid tumors have been less favorable. A growing body of research suggests that epigenetic drugs can be applied in combination with other therapies to increase efficacy and overcome tumor resistance. In this review, the progress of epigenetics in tumor progression and oncology drug development is systematically summarized, as well as its synergy with other oncology therapies, and the future directions of epigenetic drug development are described in detail.